Introducing Recursive Partitioning for Financial Classification: The Case of Financial Distress - FRYDMAN, HALINA; ALTMAN, EDWARD I.; KAO, DUEN‐LI (Journal of Finance, 1985)
ABSTRACT The purpose of this study is to present a new classification procedure, Recursive Partitioning Algorithm (RPA), for financial analysis and to compare it with discriminant analysis within the context of firm financial distress. RPA is a computerized, nonparametric technique based on pattern recognition which has attributes of both the classical univariate classification approach and multivariate procedures. RPA is found to outperform discriminant analysis in most original sample and holdout comparisons. We also observe that additional information can be derived by assessing both RPA and discriminant analysis results.